Komparasi Aplikasi Accurate Desktop dan Odoo untuk Penunjang Proses Penjualan pada Perusahaan (Studi Kasus PT. XYZ) - Mambu, Steven Edward; Setiawati, Popong (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to compare two Enterprise Resource Planning (ERP) applications, Accurate Desktop and Odoo, in supporting the sales process at PT. XYZ, a laboratory equipment distribution company. This study used a descriptive comparative method. The analysis was conducted based on criteria such as ease of use, feature completeness, integration between modules, accessibility, flexibility, and development potential. The results indicate that Odoo ERP excels in four key aspects: cloud-based accessibility, automatic integration between modules, support for team mobility, and high customization capabilities. Conversely, Accurate Desktop excels in ease of use and compliance with local accounting standards. This study recommends implementing Odoo ERP as the primary system to support PT. XYZ's sales process, as it addresses the company's needs for flexibility, integration, and operational efficiency, while also providing strategic support for business growth, faster decision-making, and increased competitiveness in the digital era.